Analisis Faktor-Faktor yang Mempengaruhi Sikap dan Keputusan Wakif dalam Berwakaf Produktif di Indonesia (Studi Kasus di Dompet Dhuafa) - Nur Rohmat Fadlil; Jaenal Effendi; Endriatmo Sutarto (Jurnal Penyuluhan, 2022)
This study aims to analyze internal factors (religiosity, knowledge, education, income) and external factors (regulations, sharia compliance, institutional credibility, institutional accountability) that influence wakif attitudes and decisions in productive waqf in Indonesia, a case study in Dompet Dhuafa Republika. In addition, it also aims to describe the characteristics of Wakif respondents. The method used to process the data is Structural Equation Modeling (SEM)-PLS version 3.0. Data was obtained by distributing online questionnaires to Wakif Dompet Dhuafa Republika. The results showed that the character of the respondents in this study was dominated by male respondents, with an age range of 20-50 years, had an undergraduate education background (S1/S2/S3), dominated by private employees, and the average income was in the range of Rp. 3 million to Rp. 6 million. This study also shows that income has a positive and significant effect on the attitude of waqf for waqf and the credibility of the institution also has a positive and significant effect on the decision of waqf for productive waqf. Thus it can be concluded that the increase in the collection of productive waqf funds is significantly influenced by the income and credibility of the institution.